Contraception for midlife women: lack of information? Lack of interest? Lack of investment? - Nancy Fugate Woods; Gloria Bachmann (BMC, 2017)
Abstract Despite the growing population of midlife women in the USA and in other economically-advantaged countries, there is scant research focusing on this population, especially regarding contraceptive choices in those at risk for unwanted or unplanned pregnancy. As women approach menopause, the increasing irregularity of their menstrual cycles and changing endocrine patterns present challenges for preventing unintended pregnancy, or, on the flip side, planning for a desired pregnancy. In this thematic series, we have brought together researchers and clinicians who address many of these tough clinical scenarios and offer suggestions not only for clinical management of optimal contraceptive choices for midlife women, but also suggestions for future research in this area.